Heterochiral Ala/(αMe)Aze sequential oligopeptides: Synthesis and conformational study. (27th March 2019) - Drouillat, Bruno; Peggion, Cristina; Biondi, Barbara; Wright, Karen; Couty, François; Crisma, Marco; Formaggio, Fernando; Toniolo, Claudio
Abstract : α‐Amino acid residues with a ϕ, ψ constrained conformation are known to significantly bias the peptide backbone 3D structure. An intriguing member of this class of compounds is (αMe)Aze, characterized by an N α ‐alkylated four‐membered ring and C α ‐methylation. We have already reported that ( S )‐(αMe)Aze, when followed by ( S )‐Ala in the homochiral dipeptide sequential motif ‐( S )‐(αMe)Aze‐( S )‐Ala‐, tends to generate the unprecedented γ‐bend ribbon conformation, as formation of a regular, fully intramolecularly H‐bonded γ‐helix is precluded, due to the occurrence of a tertiary amide bond every two residues. In this work, we have expanded this study to the preparation and 3D structural analysis of the heterochiral ( S )‐Ala/( R )‐(αMe)Aze sequential peptides from dimer to hexamer. Our conformational results show that members of this series may fold in type‐II β‐turns or in γ‐turns depending on the experimental conditions. Abstract : (αMe)Aze is an intriguing, conformationally constrained, α‐amino acid, characterized by an N α ‐alkylated four‐membered ring and C α ‐methylation. We previously reported that the homochiral dipeptide sequential motif ‐( S )‐(αMe)Aze‐( S )‐Ala‐ tends to generate the unprecedented γ‐bend ribbon conformation. We have herewith expanded this study to the preparation and 3D structural analysis of the heterochiral ( S )‐Ala/( R )‐(αMe)Aze sequential peptides from dimer to hexamer. Our conformational results show that members of this series may fold in type‐II β‐turns or in γ‐turns depending on the experimental conditions.